Increasing podiatry referrals for patients with inflammatory arthritis at a tertiary hospital in Singapore: A quality improvement project. (June 2017) - Carter, K.; Cheung, P.P.; Rome, K.; Santosa, A.; Lahiri, M.
Highlights: A structured quality improvement program can successfully improve rates of referral to podiatry for people with inflammatory arthritis and foot pain. This study found that there was low uptake of podiatry services due to its poor integration into mainstream care for people with inflammatory arthritis. Quality improvement methods used in this study can be applied to other centers globally to attenuate the unmet need for podiatry in rheumatic conditions and the under use of podiatry services. Abstract: Background: Foot disease is highly prevalent in people with inflammatory arthritis and is often under-recognized. Podiatry intervention can significantly reduce foot pain and disability, with timely access being the key factor. The aim of this study was to plan and implement a quality improvement project to identify the barriers to, and improve, uptake of podiatry services among patients with inflammatory arthritis-related foot problems seen at a tertiary hospital in Singapore. Method: A 6-month quality improvement program was conducted by a team of key stakeholders using quality improvement tools to identify, implement and test several interventions designed to improve uptake of podiatry services. The number of patients referred for podiatry assessment was recorded on a weekly basis by an experienced podiatrist. The criterion for appropriate referral to podiatry was those patients with current or previous foot problems such as foot pain, swelling and deformity. Results: Interventions included education initiatives, revised workflow, development of national guidelines for inflammatory arthritis, local podiatry guidelines for the management of foot and ankle problems, routine use of outcome measures, and introduction of a fully integrated rheumatology-podiatry service with reduced cost package. Referral rates increased from 8% to 11%, and were sustained beyond the study period. Complete incorporation of podiatry into the rheumatology consultation as part of the multidisciplinary team package further increased referrals to achieve the target of full uptake of the podiatry service. Conclusion: Through a structured quality improvement program, referrals to podiatry increased and improved the uptake and acceptance of rheumatology-podiatry services.